Análise sistêmica do processo ensino aprendizagem de Genética à luz da Teoria Fundamentada - Silva, Cirlande Cabral da (2014)
The present work concerns the teaching of genetics, because this is an area difficult to understand due to the complexity of the issues that are covered by it. Therefore, it is essential to seek alternatives, means, strategies and teaching-learning resources that may increasingly facilitate the teaching learning process of this discipline. Faced with this panorama was investigated as a substantive theory could be built to contribute to the teaching and learning of genetics in the course of Licentiate in Biological Sciences from the Federal Institute of Amazonas (IFAM). Started began our studies analyzing the first transcripts (data) from interviews with students and teachers and began to separate, classify and summarize these data by means of analytical coding (open, axial and selective), with successive questions and comparisons. The first codes are grouped, noting those already initially presented as emerging subcategories, i.e. codes with the ability to group a large amount of raw codes. In pursuit, not only our emerging sub coalesce (join), but also become systematized by hierarchical clustering. The subcategories were grouped in terms of properties and dimensions, and there was thus obtained, the first analytical categories. The relations between them provided us with a conceptual instrument on the experience studied, ie, substantive theory lecturing on the phenomenon investigated. A substantive theory was obtained convalidada and legitimized through the Delphi Method is recognized as one of the best tools for qualitative prediction. This statistical method revealed that the indicators used in the validation of the theory (interviews, codes, subcategories, categories and core category) were highly relevant to the proposed substantive theory. Importantly, the analysis of Substantive Theory has revealed a central category ("Reorienting the teaching practice") and five analytical categories which been: 1) "Diversifying the classroom to facilitate understanding"; 2) "Realizing the complexity of the subject"; 3) "Looking for the understanding of the subject"; 4) "Changing the style class", 5) "Changing the way of teaching." Analyzing the contribution of this substantive theory for teaching genetics at IFAM, can highlight two important contributions: a) The first is the continuing training of teachers of Genetics, between the Federal University of Amazonas (Amazonas University), the University of State of Amazonas (UEA) and the Federal Institute of Amazonas (IFAM) organized classroom theoretical and practical modules and non-classroom activities that would the objective to provide updates through the Genetics of contemporary themes modules approach, prioritizing a focus contextualized knowledge where teachers can restructure their knowledge and to propose and exchange experiences on teaching methodologies in this area of biology; b) The use of media and teaching resources teaching (differentiated teaching strategies), adequate but they have a theoreticalepistemological foundation from the established criteria. In other words, the methodologies applied in the teaching of genetics not only stay in the subjective field and take into account the categories found in this research.